2008
DOI: 10.1007/s00134-008-1337-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating regulatory T cells (CD4+CD25+CD127−) contribute to lymphocyte anergy in septic shock patients

Abstract: Purpose-Sepsis syndrome represents the leading cause of death in intensive care unit. Patients present features consistent with a decline in immune responsiveness potentially contributing to mortality. We investigated whether CD4 + CD25 + regulatory T cells (Treg) participate in the induction of lymphocyte anergy after sepsis. © Springer-Verlag 2008Correspondence to: Guillaume Monneret. Electronic supplementary materialThe online version of this article (doi:10.1007/s00134-008-1337-8) contains supplementary ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
194
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 263 publications
(220 citation statements)
references
References 47 publications
15
194
1
7
Order By: Relevance
“…These results indicated that this relative increase was probably caused by a decrease in effector T‐cell numbers. Recent studies indicated that an increased number of Treg cells is deleterious in sepsis and is associated with decreased effector T‐cell proliferation and function 37. Furthermore, Treg cells can also suppress innate immune cells.…”
Section: Mechanism Of Sepsis‐induced Immunosuppressionmentioning
confidence: 99%
“…These results indicated that this relative increase was probably caused by a decrease in effector T‐cell numbers. Recent studies indicated that an increased number of Treg cells is deleterious in sepsis and is associated with decreased effector T‐cell proliferation and function 37. Furthermore, Treg cells can also suppress innate immune cells.…”
Section: Mechanism Of Sepsis‐induced Immunosuppressionmentioning
confidence: 99%
“…The relative increase in circulating Tregs might play a role in lymphocyte anergy after septic shock and represent a standard surrogate marker of declining proliferative capacity after sepsis. [30] …”
Section: The Interventional Strategy Of Tregs For Sepsismentioning
confidence: 99%
“…Initialement décrite en 2003 [22], l'augmentation du pourcentage de lymphocytes T régulateurs (Treg) circulants a été largement confirmée au gré de l'amélioration de leur phénotypage par cytométrie en flux [23]. Cette élévation persiste chez les patients qui vont décéder [22].…”
Section: Augmentation Des Cellules T Régulatricesunclassified